Study of the Role of Antimicrobial Glucosinolate-Derived Isothiocyanates in Resistance of Arabidopsis to Microbial Pathogens - Tierens, Koenraad F.M.-J.; Thomma, Bart P.H.J.; Brouwer, Margreet; Schmidt, Jürgen; Kistner, Katherine; Porzel, Andrea; Mauch-Mani, Brigitte; Cammue, Bruno P.A.; Broekaert, Willem F. (My University, 2001)
Crude aqueous extracts from Arabidopsis leaves were subjected to chromatographic separations, after which the different fractions were monitored for antimicrobial activity using the fungus Neurospora crassa as a test organism. Two major fractions were obtained that appeared to have the same abundance in leaves from untreated plants versus leaves from plants challenge inoculated with the fungus Alternaria brassicicola. One of both major antimicrobial fractions was purified to homogeneity and identified by 1H nuclear magnetic resonance, gas chromatography/electron impact mass spectrometry, and gas chromatography/chemical ionization mass spectrometry as 4-methylsulphinylbutyl isothiocyanate (ITC). This compound has previously been described as a product of myrosinase-mediated breakdown of glucoraphanin, the predominant glucosinolate in Arabidopsis leaves. 4-Methylsulphinylbutyl ITC was found to be inhibitory to a wide range of fungi and bacteria, producing 50% growth inhibition in vitro at concentrations of 28 μm for the most sensitive organism tested (Pseudomonas syringae). A previously identified glucosinolate biosynthesis mutant, gsm1-1, was found to be largely deficient in either of the two major antimicrobial compounds, including 4-methylsulphinylbutyl ITC. The resistance of gsm1-1 was compared with that of wild-type plants after challenge with the fungi A. brassicicola, Plectosphaerella cucumerina, Botrytis cinerea, Fusarium oxysporum, or Peronospora parasitica, or the bacteria Erwinia carotovora or P. syringae. Of the tested pathogens, only F. oxysporum was found to be significantly more aggressive on gsm1-1 than on wild-type plants. Taken together, our data suggest that glucosinolate-derived antimicrobial ITCs can play a role in the protection of Arabidopsis against particular pathogens.